2016
DOI: 10.1002/mus.25039
|View full text |Cite
|
Sign up to set email alerts
|

Body weight-supported training in Becker and limb girdle 2I muscular dystrophy

Abstract: Anti-gravity training improved closed-kinetic-chain leg muscle strength despite no changes in isometric knee extension strength and absolute RFD. The improved closed-kinetic-chain performance may relate to neural adaptation involving motor learning and/or improved muscle strength of other muscles than the weak knee extensors. Muscle Nerve 54: 239-243, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The ability of virtual reality to create opportunities for active repetitive motor/sensory practice adds to its potential for neuroplasticity and learning in individuals with neurologic disorders 72 and can represent the future for LGMD rehabilitation. Corroborating with Jensen et al 73 hypothesis, our study agrees with their idea that people with LGMD have the potential to optimize motor function through motor learning when the training is performed in a safe environment, as is done during a virtual reality task.…”
Section: Discussionsupporting
confidence: 91%
“…The ability of virtual reality to create opportunities for active repetitive motor/sensory practice adds to its potential for neuroplasticity and learning in individuals with neurologic disorders 72 and can represent the future for LGMD rehabilitation. Corroborating with Jensen et al 73 hypothesis, our study agrees with their idea that people with LGMD have the potential to optimize motor function through motor learning when the training is performed in a safe environment, as is done during a virtual reality task.…”
Section: Discussionsupporting
confidence: 91%
“…The role of exercise in limb-girdle muscular dystrophy has been reported in previous studies which showed improvement after exercise. 13,14 The above patient also showed a good response to physiotherapy.…”
Section: A S E Pr E S E Ntati O Nmentioning
confidence: 82%
“…ESs ranged from −1.94 in the social functioning item of the 36-Item Short Form Survey (SF-36) after a multicomponent intervention 20 to 4.00, observed in lunges performance after an intervention combining aerobic and strength training. 51 …”
Section: Resultsmentioning
confidence: 99%